Consumer-Based Physical Activity Monitor as a Practical Way to Measure Walking Intensity During Inpatient Stroke Rehabilitation. Issue 9 (September 2017) - Klassen, Tara D.; Semrau, Jennifer A.; Dukelow, Sean P.; Bayley, Mark T.; Hill, Michael D.; Eng, Janice J.
Abstract : Background and Purpose—: Identifying practical ways to accurately measure exercise intensity and dose in clinical environments is essential to advancing stroke rehabilitation. This is especially relevant in monitoring walking activity during inpatient rehabilitation where recovery is greatest. This study evaluated the accuracy of a readily available consumer-based physical activity monitor during daily inpatient stroke rehabilitation physical therapy sessions. Methods—: Twenty-one individuals admitted to inpatient rehabilitation were monitored for a total of 471 one-hour physical therapy sessions which consisted of walking and nonwalking therapeutic activities. Participants wore a consumer-based physical activity monitor (Fitbit One) and the gold standard for assessing step count (StepWatch Activity Monitor) during physical therapy sessions. Linear mixed modeling was used to assess the relationship of the step count of the Fitbit to the StepWatch Activity Monitor. Device accuracy is reported as the percent error of the Fitbit compared with the StepWatch Activity Monitor. Results—: A strong relationship (slope=0.99; 95% confidence interval, 0.97–1.01) was found between the number of steps captured by the Fitbit One and the StepWatch Activity Monitor. The Fitbit One had a mean error of 10.9% (5.3) for participants with walking velocities <0.4 m/s, 6.8% (3.0) for walking velocities between 0.4 and 0.8 m/s, and 4.4% (2.8) for walking velocities >0.8 m/s. Conclusions—: This study provides preliminary evidence that the Fitbit One, when positioned on the nonparetic ankle, can accurately measure walking steps early after stroke during inpatient rehabilitation physical therapy sessions. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01915368.